Association between obesity and psychological distress in the Chilean population during the COVID-19 pandemic: Social Wellbeing Survey 2021 - Carlos González-Torres; Lydia Lera; Pablo A. Lizana (PLoS ONE, 2025)
The COVID-19 pandemic has exacerbated obesity and mental health problems, particularly anxiety and depression. Both conditions share common risk factors, suggesting a possible bidirectional relationship. This study analyses the association between obesity and psychological distress in the Chilean population during the pandemic. A secondary analysis of data from the 2021 Social Wellbeing Survey (n = 10395) was conducted using logistic regression models to examine the relationship between obesity and the presence of severe psychological distress. The prevalence of obesity and severe psychological distress was higher in women (31.85% and 7.66%) than in men (25.1% and 3.6%). Individuals with obesity had a higher risk of severe psychological distress OR 1.3 (95% CI 1.05–1.60), as did women OR 2.16 (95% CI 1.83–2.65). Conversely, individuals with severe psychological distress had a higher risk of obesity OR 1.4 (95% CI 1.19–1.71), as did women OR 1.4 (95% CI 1.26–1.51) and individuals couple/married OR 1.3 (95% CI 1.17–1.46). Additionally, higher educational levels are a protective factor for both obesity and severe psychological distress. A higher prevalence of obesity and psychological distress was observed in women and variations by age. Obesity and severe psychological distress behaved as mutual risk factors, suggesting a possible bidirectional relationship. These findings support the need for mental health interventions for at-risk groups.